Plastic deformation mechanism and hardening mechanism of rolled Rare-Earth magnesium alloy thin sheet - Deng, Jia-fei; Tian, Jing; Zhou, Yancai; Chang, Yuanying; Liang, Wei; Ma, Jinyao (Materials & design, 2022)
[Display omitted] •The shape of the precipitates affects the plastic deformation of rare earth magnesium alloy sheets and the activation of slip variants.•The competitive relationship between local strain and macroscopic strain influences the selection and activation order of slip variants.•Intragranular multi-slip and intergranular slip transfer can be used as plastic deformation mechanisms and hardening mechanisms.•Geometric compatibility is not a necessary condition for transgranular slip. The as-cast rare earth magnesium alloy is extremely difficult to be rolled due to poor plasticity. In this paper, the rolled rare earth magnesium alloy thin sheet was successfully prepared by repeated rolling with small thickness reductions in multiple passes. The microstructure evolution of rare earth magnesium alloys during rolling and forming and its plastic deformation mechanism was explored. The results show that the shape of the precipitates affects the plastic deformation of rare earth magnesium alloys. The slender precipitates can activate more types of non-basal slip to coordinate the deformation, while the agglomerated precipitates cause cracks easily. Intragranular multi-slip and inter-grain slip transfer are the plastic deformation mechanism and hardening mechanism of rolled rare-earth magnesium alloys. The competitive relationship between local strain and macroscopic strain affects the selection and activation order of slip variants, and geometric compatibility is not a necessary condition for coordinated deformation between adjacent grains. The rolled rare earth magnesium alloy sheet not only improves the strength and plasticity significantly but also breaks through the limitation of the application shape of rare earth magnesium alloy, which is of great significance for expanding the practical application of rare earth magnesium alloy in industrial production.